2020
DOI: 10.21203/rs.3.rs-87927/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Warming up Cooling Cooperators

Abstract: The warm-glow of giving is one mechanism proposed to account for high levels of human cooperation. However, little is known about how warm-glow can be harnessed to sustain long-term cooperation to benefit wider society (vaccinations, blood donation). We argue that the power of warm-glow to sustain long-term cooperation cools offs over time but can be warmed-up with a simple intervention message. We test, and confirm this prediction, in a field-based experiment (n = 5,821) comparing warm-glow versus positive af… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 72 publications
(130 reference statements)
0
12
0
Order By: Relevance
“…The results showed that those who had rebooked in centre were more likely to return 3 months later to donate, as were those who received the warm‐glow‐plus‐donor‐identity message with this effect for the warm‐glow‐plus‐donor‐identity message stronger in those who had not rebooked in the centre. Thus, this simple warm‐glow‐plus‐donor‐identity message enhanced the return rates overall and especially in those who are generally less likely to return (a low warm glow group) [28].…”
Section: Retention: Warm Glow and The Donor Experiencementioning
confidence: 99%
“…The results showed that those who had rebooked in centre were more likely to return 3 months later to donate, as were those who received the warm‐glow‐plus‐donor‐identity message with this effect for the warm‐glow‐plus‐donor‐identity message stronger in those who had not rebooked in the centre. Thus, this simple warm‐glow‐plus‐donor‐identity message enhanced the return rates overall and especially in those who are generally less likely to return (a low warm glow group) [28].…”
Section: Retention: Warm Glow and The Donor Experiencementioning
confidence: 99%
“…There is a large literature exploring the mechanisms-of-altruism (MOA) that underly voluntary non-remunerated blood donation (VNRDB). [1][2][3] Key among these are: (i) reluctant altruism, (ii) impurealtruism, (iii) warm-glow and (iv) reputation building. [1][2][3][4][5][6] Reluctant altruism refers to a preference to help when others cannot be trusted to help, especially where the number of people helping is low.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Key among these are: (i) reluctant altruism, (ii) impurealtruism, (iii) warm-glow and (iv) reputation building. [1][2][3][4][5][6] Reluctant altruism refers to a preference to help when others cannot be trusted to help, especially where the number of people helping is low. 1,2,4,6,7 This is critical for first-time donors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations